Insight into the role of slag particles in coal gasification fine slag on hierarchical porous composites preparation and CO2 capture. (15th February 2022) - Miao, Zekai; Guo, Zhenkun; Qiu, Guofeng; Jia, Wenke; Jiao, Keran; Zhang, Yixin; Wu, Jianjun
Highlights: Valued-added HTCs were prepared from FS. SP also generated the pore structure during chemical activation. Leached metal elements from SP promote the development of pore structure. FS-based HTCs exhibits excellent CO2 adsorption capacity and fast adsorption rate. Abstract: Coal gasification fine slag (FS), classified as an industrial solid waste, is composed of residual carbon (RC) and slag particles (SP). The simultaneous utilization of RC and SP to prepare hierarchical porous composite (HTC) could realize the value-added utilization of FS. The role of SP in FS on HTC preparation is extremely vital and worthy of study. In this paper, FS was successfully used to synthesize HTCs for CO2 adsorption. Orthogonal experiment was conducted to study the effect of SP on the properties of the synthesized HTCs. The changes of impregnation conditions could be effective for developing pore structure of HTCs and the surface area increased by 226 m 2 /g. Furthermore, the role of SP in FS on HTCs preparation was analyzed. After chemical activation, there was generation of many new pores in SP that the surface area and pore volume could reach 302 m 2 /g and 0.271 cm 3 /g. Besides, the leached metallic elements in the process of KOH impregnation could affect the mesopore development. The HTCs also proved to be attractive for CO2 capture. The highest CO2 adsorption capacity of 2.35 mmol/g at 25 °C was achieved with 5-PH-FSHCT sample. It also exhibited good selectivity of CO2 over N2 of 9.5. Furthermore, the sample had not only fast adsorption kinetics that it reached saturation levels in about 1.5 min, but also excellent regeneration efficiency 97% after ten cycles. All results suggest that FS has a great potential to be reused as a high performance adsorbent for practical and industrial CO2 adsorption applications.